Pharmacogenomics for neurodegenerative disorders - a focused review - Ahmad, S. Rehan; Zeyaullah, Md.; Khan, Mohammad Suhail; AlShahrani, Abdullah M.; Altijani, Abdelrhman A. Galaleldin; Ali, Haroon; Dawria, Adam; Mohieldin, Ali; Alam, Mohammad Shane; Mohamed, Awad Osman Abdalla (Frontiers in Pharmacology, 2024)
Neurodegenerative disorders such as Alzheimer's disease (AD), Parkinson's disease (PD), Huntington's disease (HD), and amyotrophic lateral sclerosis (ALS) are characterized by the progressive degeneration of neuronal structure and function, leading to severe cognitive and motor impairments. These conditions present significant challenges to healthcare systems, and traditional treatments often fail to account for genetic variability among patients, resulting in inconsistent therapeutic outcomes. Pharmacogenomics aims to tailor medical treatments based on an individual's genetic profile, thereby improving therapeutic efficacy and reducing adverse effects. This focused review explores the genetic factors influencing drug responses in neurodegenerative diseases and the potential of pharmacogenomics to revolutionize their treatment. Key genetic markers, such as the APOE ε4 allele in AD and the CYP2D6 polymorphisms in PD, are highlighted for their roles in modulating drug efficacy. Additionally, advancements in pharmacogenomic tools, including genome-wide association studies (GWAS), next-generation sequencing (NGS), and CRISPR-Cas9, are discussed for their contributions to personalized medicine. The application of pharmacogenomics in clinical practice and its prospects, including ethical and data integration challenges, are also examined.